2017
DOI: 10.15436/2378-6914.17.1540
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Function after Transradial Percutaneous Coronary Intervention Short-Term Interim Results of the ARCUS Study

Abstract: Aims: To examine the short-term effects of transradial percutaneous coronary interventions on the upper extremities function. Method and results:This is an interim analysis of the Effects of trAnsRadial perCUtaneouS coronary intervention on upper extremity function (ARCUS) study. Out of 191 patients evaluated at 2 weeks after they had undergone a transradial percutaneous coronary intervention, 120 (62.8 % ) had manifestations of upper extremity dysfunction on the side of the intervention. The main abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Studies such as ARCUS and HANGAR are the most relevant in measuring the loss of handgrip strength; however, both studies were performed in populations undergoing coronary arteriography, not necessarily with ACS diagnosis, unlike our study. 14,21 An interim ARCUS report, with a sample of 191 patients, showed upper limb dysfunction. However, the methodology used in this study differs from ours since they are based on questionnaire-type scales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies such as ARCUS and HANGAR are the most relevant in measuring the loss of handgrip strength; however, both studies were performed in populations undergoing coronary arteriography, not necessarily with ACS diagnosis, unlike our study. 14,21 An interim ARCUS report, with a sample of 191 patients, showed upper limb dysfunction. However, the methodology used in this study differs from ours since they are based on questionnaire-type scales.…”
Section: Discussionmentioning
confidence: 99%
“…However, the methodology used in this study differs from ours since they are based on questionnaire-type scales. 21 On the other hand, when measuring the handgrip strength with a dynamometer, no loss of this was demonstrated, since they used percentages instead of absolute values of the scales proposed by the ASTH. Contrary to what we did in our study, absolute values were used and showed a decrease of handgrip strength in the general population and the same way in the distribution by gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interim analysis revealed that the questionnaires, especially the DASH questionnaire, and the rigorous cut-off points of the strength measurements yielded false positive results for both extremities [15]. us, the questionnaires were excluded and the cut-off values for those measurements were modified to percentage instead of absolute change (Table 1) [15]. e modified primary endpoint was applied for the final analysis.…”
Section: Upper Extremitymentioning
confidence: 99%